P 42. ALS patients show increased T-cell activation in peripheral blood and cerebrospinal fluid. Issue 8 (August 2021) - Pawlitzki, M.; Schulte-Mecklenbeck, A.; Schreiber, S.; Vielhaber, S.; Herty, M.; Marten, A.; Pfeuffer, S.; Ruck, T.; Wiendl, H.; Gross, C.C.; Meuth, S.G.; Boentert, M.; et al.
Abstract : Objective. We investigated intrathecal and peripheral immune profiles in amyotrophic lateral sclerosis (ALS) patients compared to controls free of neurological disorders (CTRL) and patients with dementia (DEM) or primary progressive multiple sclerosis (PPMS) to elucidate whether compartment-specific inflammation contributes to ALS pathophysiology. Methods. Conventional cerebrospinal fluid (CSF) parameters were examined in 308 patients including 132 ALS patients. In a subgroup of 41 ALS patients, extensive flow-cytometric immune cell profiling in peripheral blood (PB) and CSF was performed and compared with data from 26 CTRL, 57 DEM and 27 PPMS patients. Results. ALS patients presented with significantly altered proportions of monocyte subsets in PB and increased frequencies of CD4+ and CD8+ T cells expressing the activation marker HLA-DR in PB and CSF compared to CTRL. The increased intrathecal levels of T-cell activation were comparable to DEM and PPMS and resulted from in situ differentiation rather than trans-migration from the PB. Moreover, peripheral CD4+ and CD8+ T cell HLA-DR expression significantly exceeded DEM and PPMS. While T-cell activation did not correlate with clinical measures, patients with high disease disability and rapid progression showed reduced intrathecal levels of immune-regulatory CD56bright natural killer (NK) cells. The integration of these parameters into a composite score facilitated the differentiation of patients with high ALS severity and rapid disease progression from patients from all other cohorts. Conclusion. Increased peripheral and intrathecal activation of CD4+ and CD8+ T cells concomitant with diminished immune regulation by CD56bright NK cells suggest an involvement of these immune cells in ALS pathophysiology.